Biological and Biomedical Applications of Synchrotron Infrared Microspectroscopy - Dumas, P. (Kluwer Academic Publishers, 2003)
The high brightness of synchrotron light,which is about three orders of magnitudegreater than a thermal source, has beenexploited in biological and biomedicalapplications of infrared microspectroscopy. The potential of this analytical tool isdocumented in this article in the study ofhuman tissue (hair and skin) and individualcells: biochemical and bio-structuralchanges based on corresponding functionalgroups have been identified and imaged withunprecedented spatial resolution. Thistechnique also provides a new tool foranalysis of biochemical kinetics of samplesduring disease and treatment. In the future, the combination ofinfrared microspectroscopy with othersynchrotron-based microscopic techniques,such as X-ray microscopy, at the samesample location is discussed.